The Role of Students’ Spiritual Intelligence in Enhancing Their Academic Engagement: A Theoretical Review - Qiangqiang Ma; Fujun Wang (Frontiers in Psychology, 2022)
Spiritual intelligence as a new type of intelligence has been limitedly explored in education. As it connects one’s mental and spiritual life to his/her performance and functioning, it can play an especial role in students’ L2 education. However, few studies have empirically examined this construct in relation to student-related factors like academic engagement. Against this shortcoming, the present mini-review study presented both theoretical and empirical underpinnings of this line of research by defining the concepts, their components, and previous studies. Finally, the study enumerated the existing gaps and offered future directions and implications for the educational practitioners and researchers whose awareness of spiritual intelligence and its impact on L2 education and learner-psychology variables can improve.